2008
DOI: 10.1007/s10157-008-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

A case of glomerulopathy showing podocytic infolding in association with Sjögren’s syndrome and primary biliary cirrhosis

Abstract: A 49-year-old man was admitted to our hospital with mild proteinuria. Prior to admission, he had been diagnosed as having Sjögren's syndrome in association with primary biliary cirrhosis. Examination of a renal biopsy under light microscopy revealed diffuse and global mesangial cell proliferation and a spike and/or bubbling formation of the glomerular basement membrane (GBM), resembling membranoproliferative glomerulonephritis. In contrast, immunofluorescent studies showed marked immunoglobulin and complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The relatively higher incidence of IC-PIG is consistent with previous reports. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 12 , 13 , 14 , 18 , 19 , 20 , 21 , 22 LMD/MS identified the protein ACTN4, which serves as a significant actin crosslinking cytoskeletal protein for maintaining normal podocyte structure, dramatically decreased than in the donor kidney group. Confocal microscope found that the ACTN4 and COL4A3 colocalized, which further verified that the GBM microstructures visualized in EM originated from the podocyte.…”
Section: Discussionmentioning
confidence: 95%
“…The relatively higher incidence of IC-PIG is consistent with previous reports. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 12 , 13 , 14 , 18 , 19 , 20 , 21 , 22 LMD/MS identified the protein ACTN4, which serves as a significant actin crosslinking cytoskeletal protein for maintaining normal podocyte structure, dramatically decreased than in the donor kidney group. Confocal microscope found that the ACTN4 and COL4A3 colocalized, which further verified that the GBM microstructures visualized in EM originated from the podocyte.…”
Section: Discussionmentioning
confidence: 95%
“…Reportedly, renal amyloidosis [12], podocytic infolding glomerulopathy [13], lupus-associated lesions [4], and anti-neutrophil cytoplasmic antibody-associated nephritis are known to occur in patients with SjS [4]. Treatment for renal involvement primarily includes the administration of corticosteroid, and a few patients receive other immunosuppressants such as cyclosporine, cyclophosphamide, mycophenolate mofetil, and rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy reveals infolding of the cytoplasm of the podocytes into the GBM. Most of the cases reported worldwide, indicate that PIG usually co-exists with another autoimmune disease [2,3]. In this case we present a diabetic patient with no other autoimmune disease in his medical history, whose biopsy was characterized as PIG.…”
Section: Introductionmentioning
confidence: 87%